PUSAT KULINER BERKELANJUTAN DI PANTAI INDAH KAPUK - Giacinta Fabiola; Diah Anggraini (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
The most fundamental changes in human behavioral pattern is caused by food. These changes happened since Hunter Gatherer period and evolve through Agricultural Revolution period, Industrial Revolution period, and it is still happening now. The main subject of this research is Millennials and it focuses on “How do Millenials Treat Their Food?” issue. This project is located at Pantai Indah Kapuk (PIK) Boulevard, North Jakarta which is an iconic place that serves as a culinary center for all generations. Project site is located between office complex, housing, and commercial area that has high mobility of pedestrians. The purpose of this project is to participate in giving the town the facility that it needs especially the area surrounding project site as linkage between other buildings functions and encouraging a change in Millennials’ eating habits that supports Sustainable Development Goals regarding Zero Hunger, also to preserve local ecological quality through food and plastic waste reduction. This research use Tipology, Pattern Language, Phenomenology and Field Survey research methodologies. The result of this research is designing a building as “Sustainable Food Hub at Pantai Indah Kapuk”. This project consists of 4 main programs which is Restaurant & Café, Growing Field Area, Education Platform, and Sustainable Food Utensils Shop that has a purpose of improving Millennials’ Eating Habits. It also serves as a linkage around project site as a form of project’s contribution and response to the town need for pedestrian lane. AbstrakPerubahan pola perilaku manusia yang paling fundamental disebabkan oleh makanan. Hal tersebut sudah terjadi semenjak masa Hunter Gatherer, Agricultural Revolution, Industrial Revolution dan masa kini. Millennial menjadi subyek utama bahasan dari penelitian ini. Maka fokus isu yang diangkat adalah “Bagaimana Millennial Memperlakukan Makanan?”. Lokasi proyek berada di Jl. Pantai Indah Kapuk, Jakarta Utara yang sudah menjadi ikon sebagai daerah pusat kuliner dari segala kalangan generasi. Lokasi tapak berada di antara perkantoran, perumahan dan komersil yang memiliki pergerakan mobilitas pedestrian yang tinggi setiap harinya. Tujuan dari proyek ini adalah ingin ikut serta dalam memberikan fasilitas yang dibutuhkan oleh kota terutama sekitar tapak proyek sebagai linkage di antara fungsi bangunan lainnya dan mencoba mengubah eating habits generasi Millennial yang lebih mendukung gerakan Sustainable Development Goals perihal Zero Hunger serta dapat menjaga kualitas ekologi setempat dengan cara mengurangi sampah makanan dan plastik. Metode penelitian yang digunakan pada penelitian ini adalah Tipology, Pattern Language, Phenomenology dan Survey Lapangan. Hasil penelitian yang didapatkan adalah mendesain bangunan sebagai “Pusat Kuliner Berkelanjutan di Pantai Indah Kapuk/ Sustainable Food Hub at Pantai Indah Kapuk”. Proyek ini memiliki 4 program utama yaitu Restaurant & Café, Growing Field Area, Education Platform, & Sustainable Food Utensils Shop yang bertujuan memperbaiki Millennial’s eating habits serta Linkage sebagai bentuk tanggapan proyek terhadap kebutuhan akan jalur pedestrian di sekitar tapak sehingga proyek bisa memberikan kontribusi bagi kota.